Pengaruh Human Relation Dan Lingkungan Kerja Terhadap Etos Kerja Pegawai Pada Kantor Bapelitbang Kabupaten Tabanan - Martini, Ni Made Dwi; Ayu Wimba, I Gusti; Astrama, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
One way to achieve organizational goals effectively is to develop and improve the work ethic of its members. Seeing this, this study was made to see the relationship between human relations and the work environment with work ethic, both partially and simultaneously. The research location is at the Bapelitbang Office of Tabanan Regency. 46 respondents were selected as the research sample, which later the data will be processed using multiple linear regression analysis techniques. From the test results, it was found that human relations has a significant positive relationship with work ethic, a significant positive relationship occurs between work environment and work ethic, and simultaneously human relations and work environment affect work ethic. The magnitude of the influence of independent variables on work ethic is 71.6%. Suggestions in this study are that the Tabanan Regency Bapelitbang Office is expected to always provide professional work direction, increase employee morale by creating a harmonious and pleasant work atmosphere.